"What Value Should We Attach to All These Petitions?": Petition Campaigns and the Problem of Legitimacy in the Nineteenth-Century Netherlands. Issue 3 (2019) - Janse, Maartje
Abstract : This article focuses on large-scale petitioning campaigns, or petitionnementen as they were called, organized between 1828 and 1878, including contemporary reflections and debates on this new phenomenon. Although there were only a handful of petitionnementen, they had a remarkable impact—not only on the issues at hand but also on the balance of power between Crown, Cabinet, Parliament, and people. Mass petitions necessarily challenged the political system, whose legitimacy was based on elections under a limited franchise. Based on parliamentary reports, pamphlets, and other sources reflecting on petitioning in general and the petitionnementen more specifically, this article asks how petitioners claimed legitimacy, and how politicians and other observers responded to those claims. Special attention is given to the international context within which Dutch petitioning practices developed. The article focuses on three case studies, representing the major petitioning campaigns of this period: the Southern petition movements of 1828–1830 that were a catalyst for the Belgian revolution (thus reinforcing the association between mass petitioning and revolution), the Anti-Catholic "April Movement" of 1853, and the so-called People's Petitionnement of 1878, against the liberal education law. Remarkably enough, in the Netherlands it was not progressive reformers, but most prominently conservative Orthodox Protestants who organized petitionnementen.